Complete molecular genome analyses of equine rotavirus a strains from different continents reveal several novel genotypes and a largely conserved genotype constellation - Matthijnssens, Jelle (2012)
In this study, the complete genome sequences of seven equine group A rotavirus (RVA) strains (RVA/Horse-tc/GBR/L338/1991/G13P[18], RVA/Horse-wt/IRL/03V04954/2003/G3P[12] and RVA/Horse-wt/IRL/04V2024/2004/G14P[12] from Europe; RVA/Horse-wt/ARG/E30/1993/ G3P[12], RVA/Horse-wt/ARG/E403/2006/G14P[12] and RVA/Horse-wt/ARG/E4040/2008/ G14P[12] from Argentina; and RVA/Horse-wt/ZAF/EqRV-SA1/2006/G14P[12] from South Africa) were determined. Multiple novel genotypes were identified and genotype numbers were assigned by the Rotavirus Classification Working Group: R9 (VP1), C9 (VP2), N9 (NSP2), T12 (NSP3), E14 (NSP4), and H7 and H11 (NSP5). The genotype constellation of L338 was unique: G13-P[18]-I6- R9-C9-M6-A6-N9-T12-E14-H11. The six remaining equine RVA strains showed a largely conserved genotype constellation: G3/G14-P[12]-I2/I6-R2-C2-M3-A10-N2-T3-E2/E12-H7, which is highly divergent from other known non-equine RVA genotype constellations. Phylogenetic analyses revealed that the sequences of these equine RVA strains are related distantly to nonequine RVA strains, and that at least three lineages exist within equine RVA strains. A small number of reassortment events were observed. Interestingly, the three RVA strains from Argentina possessed the E12 genotype, whereas the three RVA strains from Ireland and South Africa possessed the E2 genotype. The unusual E12 genotype has until now only been described in Argentina among RVA strains collected from guanaco, cattle and horses, suggesting geographical isolation of this NSP4 genotype. This conserved genetic configuration of equine RVA strains could be useful for future vaccine development or improvement of currently used equine RVA vaccines.